PROFESIONALISME GURU BAHASA BALI PADA MASA PANDEMI - I Nyoman Suka Ardiyasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This article analyzes the professionalism of Balinese language teachers during the pandemic. The analysis process is carried out by conducting relevant studies by adapting indicators of professional teachers in general and then adapting them to Balinese language teachers. This article takes pictures of professional Balinese teachers during the pandemic which is indeed a challenge for every subject teacher. The results of the analysis found that there were ten indicators of professional teachers covering aspects of language use, learning approaches, classroom management, mastery of materials, mastery of technology. Information and the ability of teachers to motivate students.keywords: professionalism, Balinese language teacher.